HOW FOREGN DIRECT INVESTMENTS DRIVE TRADE FLOWS IN EMERGING ECONOMIES (Third Sector Social Economic Review, 2021)
This study examines how FDI determines foreign trade in emerging market economies, including Turkey, India, China, Mexico, Brazil, and Indonesia, for 1979-2019. The hidden panel cointegration results show that there is a long-term relationship between FDI and exports in these countries. The results also indicate the existence of a cointegration relationship in both directions (increase and decrease together) between imports and exports in the long run. The existence of an asymmetrical relationship between FDIs and exports confirms this fact. The departure of FDIs causes a decrease in the exports of these countries. However, there is no positive bidirectional causality relationship between FDIs and exports and imports. In addition, there is no bidirectional causality relationship between imports and exports. The results of the analysis reveal that FDIs are not the primary determinant of foreign trade in the long run.
Keywords: Foreign Direct Invesments; Trade Flows; Emerging Economies; Hidden Panel Cointegration; Asymmetric Causality Test